Social factors affecting water supply resilience to disasters. (July 2019) - Balaei, Behrooz; Wilkinson, Suzanne; Potangaroa, Regan; Adamson, Carole; Alavi-Shoshtari, Maryam
Abstract: The supply of water following disasters has always been of significant concern within communities. Although water systems encompass physical components, a variety of social, economic, and organizational factors can affect their resilience to disasters. This paper proposes an innovative indicator-based resilience quantification model and utilizes a novel framework to identify the social variables affecting water supply resilience to disasters. The CARE model is utilized in this study to understand the building blocks of water supply system resilience to disasters. The relevant factors, indicators, and sub-indicators were gathered through a comprehensive literature review, verified and ranked through a series of interviews with water supply and resilience specialists, and social scientists and economists. The study identified seven indicators for the social attributes of communities that affect water supply resilience. The indicators are the Giving Index, homicide rate, assault rate, inverse trust in army, inverse trust in police, mean years of school, and perception of crime. These indicators were tested in Chile and New Zealand, which experienced earthquakes in 2010 and 2011 respectively. The proposed indicators were found to well explain the difference in water supply resilience between the two countries.